Anterior Cruciate Ligament Reconstruction Using an "Out to In" Femoral Tunnel With Flexible Reamers: A Technical Note. Issue 1 (March 2015) - Gohil, Satyen; Martineau, Paul; Burman, Mark
Abstract : Anatomic femoral tunnel placement can be achieved by transtibial, medial portal drilling, far medial portal drilling, or "out to in" techniques percutaneously or by using open techniques. This paper describes the use of an "out to in" percutaneous technique using flexible guidepins and reamers for creating an anatomic femoral tunnel. There is no need for knee hyperflexion or an accessory portal. It is useful in revision surgery and in obese patients where hyperflexion is difficult to achieve.